Materialism and indebtedness of low income consumers: Evidence from South Africa's largest credit granting catalogue retailer - G. Jacobs; E. V.D.M. Smit (South African Journal of Business Management, 2010)
In South Africa, studies have found changes in consumption and credit usage over time to be significant amongst low-income consumers. Yet, there has been limited empirical research on consumer behaviour in South Africa and even less on low-income consumerism. This study, which explores the relationship between materialism and indebtedness among a sample of low-income, instalment paying consumers of South Africa's largest catalogue retailer, aims to augment our understanding of these phenomena, whilst making some international comparisons.The study assesses whether (i) consumers display strong characteristics of materialism and (ii) whether materialism is a significant variable in predicting the consumers‟ propensity for incurring debt. It is concluded that low-income consumers are indeed highly materialistic. The study further suggests the presence of statistically significant relationships between consumers' levels of indebtedness and the demographic variables age and gender. However, materialism and monthly income are not significant in determining a consumer‟s level of indebtedness.While the decision to conduct the study on client data from one particular retailer, limits the extent to which the findings can be generalised to the larger South African population, the results do provide a number of important insights, which contribute to the scant body of literature on low-income consumer behaviour in the RSA.
Keywords: 650